1997
DOI: 10.1063/1.473281
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxy and chainlength dependent strain in self-assembled monolayers

Abstract: We use grazing incidence x-ray diffraction to systematically study the structure of an archetypal self-assembled monolayer as a function of the hydrocarbon chain length, n. The monolayers consists of n-alkyl thiol molecules, CH3(CH2)n−1SH (Cn, 10⩽n⩽30), self-assembled on single crystal Au(111) surfaces. At room temperature, the 2D structure is described by a C(4×2) unit mesh for all chain lengths. However, we demonstrate that there is a systematic dependence of the tilt structure (i.e., the tilt angle and tilt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
166
2
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(191 citation statements)
references
References 34 publications
22
166
2
1
Order By: Relevance
“…The measurements also reiterate the importance of secondary structure in macromolecular activity. SAM structure and packing, which are strongly influenced by chain length (39,40), have a strong control on calcite nucleation. A recent molecular dynamics analysis suggests these effects may be related to the degree of symmetry in interactions between SAM monomers and its impact on SAM order, highlighting once again the importance of cooperativity in both SAM-crystal-binding and templatedirected nucleation (35).…”
Section: Significancementioning
confidence: 99%
“…The measurements also reiterate the importance of secondary structure in macromolecular activity. SAM structure and packing, which are strongly influenced by chain length (39,40), have a strong control on calcite nucleation. A recent molecular dynamics analysis suggests these effects may be related to the degree of symmetry in interactions between SAM monomers and its impact on SAM order, highlighting once again the importance of cooperativity in both SAM-crystal-binding and templatedirected nucleation (35).…”
Section: Significancementioning
confidence: 99%
“…This tilt angle (α) is found to be 30°with respect to the surface normal toward the nearest neighbor direction. Fenter et al demonstrated a systematic dependence of the tilt structure (tilt angle and direction) with the chain length, which is explained as due to the change in intralayer interaction strength [23]. The twist angle β (which defines the rotation of the carbon chain backbone about the chain axis with respect to the plane defined by the chain axis and the surface normal) for the long-chain alkanethiol is found to be ~52°, which implies that Au-S-C bond angle is nearly 120°, close to the optimum value for the sp 2 hybridized sulfur atoms.…”
Section: Adsorption and Structure Of Samsmentioning
confidence: 99%
“…This tilt angle ðÞ is found to be 308 with respect to the surface normal towards the nearest-neighbour direction. Fenter et al demonstrated a systematic dependence of the tilt structure (tilt angle and tilt direction) on the chain length, explained as being due to the change in intralayer interaction strength [108]. The twist angle (defines the rotation of the alkyl carbon backbone about the chain axis with respect to the plane defined by the chain axis and the surface normal) for the long-chain alkanethiol is found to be $528, which implies that Au-S-C bond angle is nearly 1208, close to the optimum value for the sp 2 -hybridized sulphur atoms.…”
Section: Structure Of Sams: An Overall Viewmentioning
confidence: 99%